1990
DOI: 10.1002/1097-0142(19900115)65:2<322::aid-cncr2820650223>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the central nervous system. An unresolved therapeutic problem

Abstract: From January 1979 to December 1987, 35 cases of primary central nervous system lymphoma (CNS-L) were treated. We recently reviewed these cases focusing on treatment results, treatment modalities, and radiotherapy (RT) or chemotherapy-radiotherapy (CT-RT). Variables such as age, risk factors, presenting symptoms, and histologic condition (all were high-grade or intermediate-grade non-Hodgkin's lymphomas [NHL]) and radiologic data were similar to those of series reported previously. The median survival time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 27 publications
(6 reference statements)
2
11
0
Order By: Relevance
“…Primary CNS non-Hodgkins lymphomas are rare tumors that represent 0.5% to 1.2% of all CNS tumors and about 2% of all lymphomas [3][4][5][6]. Primary CNS lymphomas account for > 90% of all parenchymal CNS lymphomas, whereas the overwhelming majority of leptomeningeal lymphomas arise from metastatic systemic non-Hodgkins lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary CNS non-Hodgkins lymphomas are rare tumors that represent 0.5% to 1.2% of all CNS tumors and about 2% of all lymphomas [3][4][5][6]. Primary CNS lymphomas account for > 90% of all parenchymal CNS lymphomas, whereas the overwhelming majority of leptomeningeal lymphomas arise from metastatic systemic non-Hodgkins lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemotherapeutic regimens have been evaluated in the treatment of immunocompetent patients with primary CNS lymphoma both in the adjuvant and recurrent setting [1,[3][4][5][6][12][13][14][15][16][17]. Given the large number of drugs active against extraneural non-Hodgkins lymphoma, it is not surprising to find a variety of drugs employed against primary CNS lymphoma.…”
Section: Personality and Psychiatric Manifestations; 3) Focal Neurolomentioning
confidence: 99%
“…Murray et al recorded a male: female ratio of 1.5 : 1 among the 693 cases reviewed. More recent reports of PCNSL estimate the male: female ratio as ranging between 1 : 1 and 4 : 1 (Hochberg & Miller 1988;Brada et al 1990;Socie et al 1990;Neuwelt et al 1991;DeAngelis et al 1992a;Rosenthal et al 1993;Tomlinson et al 1995;Glass et al 1996;Trans-Tasman Radiation Oncology Group 1996;Cher et al 1996;Brada et al 1998;Wagner et al 1998). This slight male predominance mirrors the male predominance noted in systemic lymphomas (DeVita et al 1997).…”
Section: Sex Distributionmentioning
confidence: 99%
“…The age range in this series was 2 months to 90 years. More recent series have reported median ages at diagnosis ranging from 48-58 years (Hochberg & Miller 1988;Socie et al 1990;Neuwelt et al 1991;DeAngelis et al 1992a;Rosenthal et al 1993;Tomlinson et al 1995;Glass et al 1996;Trans-Tasman Radiation Oncology Group 1996;Cher et al 1996;Brada et al 1998;Wagner et al 1998). Reports of PCNSL in childhood are rare and are usually associated with inherited or acquired immunosuppression (Helle et al 1984;Epstein et al 1988;Kai et al 1998).…”
Section: Age Distributionmentioning
confidence: 99%
“…Attempts to improve results with combined radivt herapy and chemotherapy have been reported in eight small pilot studies using different types of chemotherapy drugs prior to or following radiotherapy (41,84,(89)(90)(91)(92)(93). Fivc of these studies reported a longer median survival (20 + to 60 months) with combination therapy than with radiotherapy alone (41, 84, 89-91).…”
Section: Primarv Cns Lymphomamentioning
confidence: 99%